Design and development of productivity rate for automated flow line in rotor arrangement with serial-parallel action analysis system (parapas) : graphical user interface (GUI) application / Jackson Khneoh Lee Jieat - Jackson, Khneoh Lee Jieat (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Productivity can be classified into three main perspectives, economical, industrial and manufacturing. In manufacturing perspective, productivity is known as the productivity rate and it is important as it directly proportional to the profit of company. Therefore, the measurement of productivity rate is needed for a company to carry out their production planning.